2012
DOI: 10.3899/jrheum.111061
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Male and Female Systemic Lupus Erythematosus in a Multiethnic Population

Abstract: Objective Male patients with systemic lupus erythematosus (SLE) are thought to be similar to female patients with SLE, but key clinical characteristics may differ. Comparisons were made between male and female patients with SLE in the Hopkins Lupus Cohort. Methods A total of 1979 patients in the Hopkins Lupus Cohort were included in the analysis. Results The cohort consisted of 157 men (66.2% white, 33.8% African American) and 1822 women (59.8% white, 40.2% African American). The mean followup was 6.02 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
133
6
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 28 publications
(57 reference statements)
29
133
6
3
Order By: Relevance
“…In general, differences between males and females were more numerous and striking in whites, especially with respect to lupus nephritis, abnormal serologies and thrombosis. 9,10 In a report presented by Cefle et al; in male patients with SLE, renal and pulmonary involvement, cardiomyopathy, serositis, discoid rash, and antiphospholipid syndrome were more frequent and the course of the disease was more severe. 11 It is mentioned that in another study; male patients with SLE present more cardiovascular comorbidities and also more serositis, adenopathies, splenomegaly, renal involvement, convulsion, thrombosis and lupus anticoagulant positivity than women.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In general, differences between males and females were more numerous and striking in whites, especially with respect to lupus nephritis, abnormal serologies and thrombosis. 9,10 In a report presented by Cefle et al; in male patients with SLE, renal and pulmonary involvement, cardiomyopathy, serositis, discoid rash, and antiphospholipid syndrome were more frequent and the course of the disease was more severe. 11 It is mentioned that in another study; male patients with SLE present more cardiovascular comorbidities and also more serositis, adenopathies, splenomegaly, renal involvement, convulsion, thrombosis and lupus anticoagulant positivity than women.…”
Section: Discussionmentioning
confidence: 97%
“…In the same study, anticardiolipin and anti-β2-glycoprotein I antibodies levels were found to be higher, although not reaching statistical significance, and thrombotic events were also seen more frequently in male patients. 10 In another study with a high number of patients; deep vein thrombosis and pulmonary embolism were found to be significantly higher in patients with SLE than in the general population. …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Male SLE patients are more likely to have end organ damage, including neuropsychiatric, renal, cardiovascular, peripheral vascular disease, and myocardial infarction. Therefore, males have higher mortality [7]. However, the precise reason for why male SLE appears to be more severe is unknown [8].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, 4-22 % of SLE occurs in males [7]. Male SLE patients are more likely to have end organ damage, including neuropsychiatric, renal, cardiovascular, peripheral vascular disease, and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%